Students’ Voices On The Implementation of Student Exchange Programs - Luneto, Sri Puput; Talib, Rasuna; Badu, Helena (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to explore students’ voices regarding the strengths and weaknesses of student exchange programs implementation (PMM-MBKM). This study was conducted through the experiences of fifth-semester students of the English Language Education Study Program (ELESP) in the academic year 2021/2022. The study involved 12 participants who attended five universities in Indonesian institutions (UST Yogyakarta, UNDIKSHA Bali, UNTAG Surabaya, UAD Yogyakarta, and UMT Banten). The method used was descriptive qualitative, based on semi-structured interviews. Overall, several aspects were identified by the respondents as potential areas in improving the PMM-MBKM of the ELESP program, including suggestions to increase the quota and transform the Nusantara Module course into a Community Service Program (KKN), the timely disbursement of funds, policy evaluation, enhancement of communication between operators and students, adaption of regulations, and refinement of the academic data input process. In practice, these findings can assist the department in providing ELESP students with written information on the strengths and weaknesses of the program implementation and a framework for improvement.